Kajian Keharaman Riba dalam Islam dan Kecenderungan Memilihnya - Devid Frastiawan; Muhammad Ghozali (University of Darussalam Gontor, 2016)
The economic system of usury which is getting stronger grip in every area of the economy in different parts of the world make it as a major threat to ruin. Crisis, inequality, social problems and the deterioration of the business climate is the result of a small proportion of the economic system of usury which still dominates the current economic system. Assess community views the money as a result of commodity pivoting money flow towards the usury-based banking will get a calculation of a fixed profit without having to bear the burden and risks. Most people consider between usury and revenue sharing is no difference. Conventional Bank that provides interest is definitely more interested in the community than the existing revenue sharing system in Islamic banks. Blessing is not the main goal in seeking sustenance, halal and haram were ignored again and took advantage by unjustly perceived as something natural. Usurious economic system which tends to be formerly known as compared with an Islamic economic system, dominates both in terms of literature, influence, and its use in most countries in the world and brought great changes to the views of the community. The perspective is then always behind every attitude and action of the community’s economy was always likely to usury. Although the community is aware of and understand the impact of usury but the reality of the matter is usury continues to be an option.